Lampedusa. Memorial for the Shipwreck of the 3rd of October, 2013 - Vincenzo Latina (Histories of Postwar Architecture)
The report will describe an environmental recovery project carried out in an abandoned quarry in the island of Lampedusa, slightly embedded in the rock and overlooking the sea. It is a striking witness of the southernmost strip of land in Europe. This stretch of sea is the tragic "theatre" of people’s migrations, of their hopes, anxieties, dramas, joys and sorrows, of humanity seeking for hope. At the same time the place is ideal to host collective events, it is a place of metaphysical suspension, suitable for quiet reflection, it is a witness-place for performances (events) and meetings. Targeted interventions have been carried out by the inclusion of minimal contemporary "grafts" in order to activate, through their otherness, new relationships between the new and the existing. The new has a laconic and essential character, therefore timeless, with a dry and minimal design, and evokes images and imaginaries of some important international events that have made the island of Lampedusa similar to a collective "theater". The key words of the project might be: essential, poetic, laconic, sustainable, accessible. On 3rd October, 2013 near the coast of Lampedusa there was a shipwreck with a tragic epilogue of 368 dead and 20 missing. On the wall in contact with the coast, 368 holes were made, they look like air bubbles frozen in the rock which are trying to reach the surface. It is the transposition of a seabed. The holes will be lit with wax lights at dusk and throughout the night, following a laic ritual. They will become like stars in the constellation. The loss, the absence of the hole in the wall becomes presence, becomes light. Death is transformed into life, hope.